Demographic Composition of Select Oncologic New Molecular Entities Approved by the FDA Between 2008 and 2017. Issue 5 (14th September 2018) - Ramamoorthy, Anuradha; Knepper, Todd C.; Merenda, Christine; Mendoza, Martin; McLeod, Howard L.; Bull, Jonca; Zhang, Lei; Pacanowski, Michael
Abstract : Race, ethnicity, sex, and age are demographic factors that can influence drug exposure and/or response, and can consequently affect treatment outcome. We evaluated demographic subgroup enrollment patterns in new therapeutic products approved by the US Food and Drug Administration (FDA) for the treatment of select cancers—breast, colorectal, lung, and prostate—that have comparative differences in morbidity and/or mortality among some demographic subgroups. In submissions of products approved between 2008 and 2013, participants ( n = 22, 481) were white (80%), from outside the United States (74%), between 17 and 64 years old (59%), and men (56% and 53%, including and excluding sex‐specific indications, respectively). In pivotal trials of products approved between2014 and 2017, participants ( n = 3, 612) were white (71%), between 17 and 64 years old (61%), and men (48% and 63%, including and excluding sex‐specific indications, respectively). The US‐relevant minority populations were under‐represented. A broader representation of patient subgroups in clinical trials may contribute to better understanding of exposure and/or response variability, and consequently help personalize drug therapy.